PENGARUH MEDIA “QUIZIZ” TERHADAP HASIL BELAJAR SANITASI HYGIENE MAKANAN DALAM PEMBELAJARAN DARING MAHASISWA - Mufidah, Lina -; Rachmawati, Eka (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
Online learning provides various conveniences, such as time flexibility, access efficiency, and cost savings for students. However, in practice, online learning often faces various challenges. The main challenges include low student engagement and motivation, limited interaction between lecturers and students, and difficulty in comprehensively evaluating students' understanding. This study aims to examine the effect of Quizizz as a learning medium on learning outcomes in an online learning setting.The research employed a quantitative approach with an experimental research design of the One Group Pretest-Posttest type. The sample consisted of 30 students in a single group. The data collection technique used in this study was a learning outcomes test, which was used to measure students' understanding of the material before and after the intervention using Quizizz. Data analysis was conducted using a t-test. The results of the study showed a significance value (Sig.) of 0.001, indicating that the use of Quizizz as a learning medium had a significant effect on students' learning outcomes. This value is smaller than the predetermined significance level (α = 0.05), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha).